Cellphone banking adoption and continuance of use in an internet banking context : a study of consumers'cross-channel cognitive evaluations - Nel, Jacques (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.